2008
DOI: 10.1002/rcm.3745
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator mass spectrometry 14C determination in CO2 produced from laser decomposition of aragonite

Abstract: Determination of 14 C in aragonite (CaCO3) decomposed thermally to CO2 using an yttrium-aluminum-garnet doped neodymium laser is reported. Laser decomposition accelerator mass spectrometer (LD-AMS) measurements reproduce AMS determinations of 14 C from conventional reaction of aragonite with concentrated phosphoric acid. The lack of significant differences between these sets of measurements indicate that LD-AMS radiocarbon dating can overcome the significant fractionation that has been observed during stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The pressure was measured directly at the gas inlet of the cell with a miniature piezoresistive pressure transducer (Keller AG, Switzerland). Using this value, the known volume of the ablation cell and the amount of carbonate removed from the sample specimen, a maximum CO 2 yield of about 70% was calculated, which is significantly higher than observed in the previous study [30]. It is also more than estimated from the previous LA-ICPMS measurements.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The pressure was measured directly at the gas inlet of the cell with a miniature piezoresistive pressure transducer (Keller AG, Switzerland). Using this value, the known volume of the ablation cell and the amount of carbonate removed from the sample specimen, a maximum CO 2 yield of about 70% was calculated, which is significantly higher than observed in the previous study [30]. It is also more than estimated from the previous LA-ICPMS measurements.…”
Section: Resultsmentioning
confidence: 89%
“…In that pilot study CO 2 was produced using a commercial 213 nm LA system, flushed onto a CO 2 trap, graphitized and subsequently measured as a conventional solid AMS target. Although the study demonstrated the principal applicability of LA sampling for radiocarbon analyses of carbonates, the suggested method could not benefit from the latest developments of online injection of CO 2 into an AMS gas ion source [30]. A pulsed laser system offers the possibility to produce CO 2 from carbonates at a rate that allows direct feeding of the CO 2 into an AMS gas ion source.…”
Section: Introductionmentioning
confidence: 99%
“…Loaded into the titanium plate are stainless steel mesh wells, each containing a bed of 20 mg of CuO powder, which serves as an oxidizing reactor to convert sample carbon to CO 2 . After the wells are packed with CuO, the plate is heated in an oven at $750°C for several hours with a continuous flow of O 2 through the oven to oxidize any organic material contaminating the CuO and maximize the amount of adsorbed O 2 [4]. The baked plates are then stored in argon to avoid atmospheric contamination.…”
Section: Sample Preparation and Methodsmentioning
confidence: 99%
“…The first otolith analysed (RS07) was sampled beyond the initial milled core 14 C measurement and into the growth zone sequence using the micromill. This series of samples was analysed by gas AMS (Rosenheim et al 2008;Wacker et al 2013). In this timeefficient online approach, the carbonate samples are placed in septum-sealed vials under a helium atmosphere.…”
Section: Gas Amsmentioning
confidence: 99%